Implementasi Design Sprint Pada Aplikasi Cowin Berbasis Mobile - Siti Asyura; Rika Perdana Sari (ABEC Indonesia, 2021)
Cowin is an investment platform in the cattle breeding sector and has been operating for several years in Pekanbaru. Currently, Cowin wants to increase its business development by expanding its target market by creating a mobile-based investment application. Since its beginning, Cowin has had a website application to make it easier for investors to invest online. However, according to the user specifications before implementing design sprint, the features contained in the website application are considered impractical to use, because they do not have much time to see cattle monitoring routinely through the website. So the purpose of this study is to identify investor's needs and problems when they want to invest in Cowin to build a good mobile-based application. The results of this study is a mobile-based Cowin application that has validated three times consisting of 2 times the task completion rate and 1-time usability testing using a likert scale. Through this research, the mobile applications that have been built is easy to learn and understand, but still need improvements in branding in the future so the investors will be interested in recommending this application to others.